Study of the dynamics of hygienic, periodontal and dental status in different population groups - S. B. Ulitovskiy; A. A. Vasyanina; O. V. Kalinina; E. S. Alekseeva; A. A. Leontiev; L. I. Pankratieva; A. V. Shevcov; A Yu. Gulieva; A. V. Antipova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Introduction. The study of the main dental statuses begins with the determination of indicators of the state of quality of oral hygiene and periodontal tissues. Given these factors, dentists should choose the most suitable for use in the appropriate age-sex and professional groups, taking into account the existing harmful factors of the external and internal environment, and occupational hazards.The objective was to determine the hygienic and dental status in different population groups by studying the parameters of the main dental diseases and to draw a parallel between them and the level of hygienic knowledge in these groups, for the correction of hygiene and preventive measures as the main way to prevent these diseases.Methods and materials. The study involved 307 people who were not burdened with general somatic pathology, of which 6 age groups were formed. Dental status was determined using the Green-Vermillion hygiene index, PMA and Mühlemann and Son periodontal indices. In order to study the level of hygienic knowledge and skills of the population, a survey was conducted using a Questionnaire and its assessment by the index of hygienic knowledge of S. B. Ulitovskiy.Results. As a result of the study, a decrease in the Green – Vermillion index was found in group 1 from (2.13±0.38) to (1.07±0.27), in group 5 – from (2.83±0.14) to (0.75±0.09); in group 6, the index at the beginning of the study was (3.47±0.12), and by the end, it decreased to (1.93±0.05), which reflects an increase in the cleansing efficiency in various groups of the population. The positive dynamics of the anti-inflammatory efficiency was observed in the 1st group from (16.81±3.52) to (8.15±1.64) %; in the 5th group, indicators has decreased by 3 times, from (18.86±0.65) to (6.53±0.77) %, in the 6th group – from (19.24±0.43) to (7.01±1.19) %. As a result of the study, it was found that the state of periodontal tissues in the 6th group according to the index of bleeding Mühlemann and Son was (9.21±2.33) %, and by the end of the study reached (5.49±1.63) %, in the 5th group – from (11.29±1.98) to (5.31±1.62) %; in the 2nd group, the indicators for the index of bleeding decreased from (11.67±0.69) to (5.00±0.28) %. In the groups, there was a decrease in the survival of hygienic knowledge, which determined the need for dental education among the population in different age groups.Conclusion. Application of individual hygienic programs of prevention of dental diseases on the basis of consistently performed hygienic procedures using various means of oral hygiene confirms the effectiveness of the activities taking into account personal hygiene indicators and dental status.Authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.